Use of Secondary Crystallization and Fly Ash in Waterproofing Materials to Increase Concrete Resistance to Aggressive Gases and Liquids - Rostislav Drochytka; Matej Ledl; Jiri Bydzovsky; Nikol Zizkova; Johannes Bester (Advances in Civil Engineering)
This paper describes the use of cement-based waterproofing screed and waterproofing coating, in which 10% of the original amount of cement was replaced by fly ash and 2% of the crystallization admixture was added by weight of cement, as a mean of protection of concrete against aggressive environments. The modified materials were applied to the underlying concrete and subjected to testing of physical and mechanical properties after exposure to effects of aggressive environments for up to 18 months. The results of the analysis have shown that after the application of waterproofing materials, there is a sufficient development of the crystals in the underlying concrete to enhance its durability. Thus, it is possible to use fly ash functionally and efficiently in polymer cement systems as a substitute for the cement together with the crystallization admixture.